Gemination in Bangla: An optimality Theoretic Analysis - Kar, Somdev (Dhaka University Journal of Linguistics, 2009)
This paper attempts to identify and analyze different types of gemination processes in Bangla. The focus is mainly on the phonological representation of sound combinations which forms a set of valid geminates in this language. I argue for three major types of gemination processes present in modern Bangla and a stratification strategy for the relavant lexical items based on their origin (SB, NB and OB, depending on the native vs. two type of borrowings). An analysis of these gemination processes are given in the framework of optimality theory (OT). Therefore, the constraint-based analysis of OT is organized in a threefold argument structure for each stratum. The conclusion is drawn towards an understanding of gemination processes of Bangla for different categories of lexical items and their phonological formuations. DOI: 10.3329/dujl.v1i2.3718 The Dhaka University Journal of Linguistics: Vol. 1 No.2 August, 2008 Page: 87-114